2016
DOI: 10.1007/s00192-016-3223-1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired contraction and decreased detrusor innervation in a female rat model of pelvic neuropraxia

Abstract: Introduction and hypothesis Bilateral pelvic nerve injury (BPNI) is a model of post-radical hysterectomy neuropraxia, a common sequelae. This study assessed the time course of changes to detrusor autonomic innervation, smooth muscle (SM) content and cholinergic-mediated contraction post-BPNI. Methods Female Sprague-Dawley rats underwent BPNI or sham surgery and were evaluated 3, 7, 14 and 30 days post-BPNI (n=8/group). Electrical field stimulated (EFS) and carbachol-induced contractions were measured. Gene e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…An important degenerative sign was vacuolisation of the sarcoplasma, which was markedly more frequent in BPNI bladders. However, we describe an increased detrusor thickness and increased bladder-to-body weight ratio after injury, suggesting detrusor hypertrophy, similar to previous studies [12,18]. Therefore, we hypothesise that detrusor hypertrophy compensates for the degenerative changes of the muscle we observed after BPNI.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…An important degenerative sign was vacuolisation of the sarcoplasma, which was markedly more frequent in BPNI bladders. However, we describe an increased detrusor thickness and increased bladder-to-body weight ratio after injury, suggesting detrusor hypertrophy, similar to previous studies [12,18]. Therefore, we hypothesise that detrusor hypertrophy compensates for the degenerative changes of the muscle we observed after BPNI.…”
Section: Discussionsupporting
confidence: 91%
“…Although detrusor contractility to direct depolarisation and parasympathetic stimulation was preserved, nerve‐induced contractility was reduced during overflow incontinence with only partial recovery in the DU phase. This is in line with previous reports of preganglionic neural crush injury, where partial functional recovery was observed but morphological recovery could not been objectified . Of interest, Payne et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2,15 The multifactorial etiology complicates the development of animal models to study this bladder disorder, as shown by the diversity of animal models 16 : aging models, 17 diabetic bladder dysfunction, 18 bladder outlet obstruction (BOO), 19 bladder ischaemia, 20 and neurogenic models. 21,22 Many of these neurogenic models, including ours, investigate UAB in FIGURE 4 PCR analysis. A, No difference in aSMA expression was found between sham and PNI bladders.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several published studies reported as a UAB model by using pelvic nerve crash- or cryoinjury (unilaterally or bilaterally) [ 92 93 94 95 96 ], in which detrusor contractility was remarkably impaired. In case of bilateral pelvic nerve injury by complete resection, the animals showed severe nervous dysfunctions, which were resemble to the situation with SCI [ 95 ].…”
Section: Animal Models For Underactive Bladdermentioning
confidence: 99%